Rozwiązywanie emocjonalnych problemów dzieci w szkole podstawowej - Miroslava Adamík Šimegová (Jesuit University Ignatianum in Krakow, 2011)
This contribution deals with the current issue of emotional problems and disorders of pupils at primary school from the point of view of the specific tasks and their solutions (prevention, diagnostics, counselling, intervention). It clarifies some specific emotional problems of pupils, defines them from the point of view of comparison of emotional disorders and brings findings from this particular problem coming from case studies. In this contribution we also discuss some specifics and problems of work of professional school staff at primary school, mainly school psychologist, in the field of solving emotional problems of pupils at primary school.